Réflexions pour une architecture significative : Univers symbolique et matériel de la maison chez les Inuit du Nunavik (Note de recherche) - Bayle, Myrtille (Études Inuit Studies, 2020)
The relationship between the Inuit inhabitants of Nunavik and their dwellings has changed significantly with the advent of sedentarization and state-run housing production. The link between the form of the house and social life has been lost in favour of a standardization of housing that leaves little room for the integration of local practices and cultural values of the inhabitants. Thus, in a context where the relationship between inhabitants and their dwellings is marked by a gap between the space designed by the authorities and the space perceived and lived by the inhabitants, how can we encourage the integration of the symbolic meanings and essential qualities of Inuit housing in order to contribute to the design of meaningful architecture for the inhabitants? This article presents the preliminary results of a literature review that aims to identify Inuit cultural values, practices and definitions of habitat, as well as the expectations of inhabitants in terms of architectural qualities and experience. Through the literature analyzed, the house as a symbolic Inuit representation is presented as a piece of the universe that is part of nuna, the land inhabited by the Inuit, and that testifies to the collective belonging to the territory. The house is also defined as a protective body and an anchoring point that participates in the elaboration of the group’s identity and socio-cultural values. It is a social space that unfolds as a collective space, open to all, and which is defined above all by social relations. This analysis of the house confirms the confrontation of a nomadic practice of space in a sedentary environment and also highlights the importance of encouraging the integration of the inhabitant in the production of his dwelling. La relation qu’entretiennent les habitants Inuit du Nunavik avec leur habitation a fortement évolué avec la sédentarisation et l’arrivée de la production du logement gérée par l’État. Le lien entre la forme de la maison et la vie sociale s’est perdu à la faveur d’une ...